«Pseudomonas fluorescens» mediated antifungal activity against «Rhihzoctonia solani» causing sheath blight in rice - Babu Submanianan; Radjacommare, Ramalingan; Samiyappan, Ramasamy; Nanadakumar, Rangaraj; Raguchander, Thiruvengadam (Phytopathologia Mediterranea, 2002)
Antifungal activity of Pseudomonas fluorescens strains PF1, FP7 and PB2 was tested against the rice sheath blight pathogen Rhizoctonia solani. The bacterial strains produced antibiotic 2,4-diacetyl phloroglucinol, iron chelating siderophore, hydrogen cyanide, lytic enzymes, such as chitinase and β-1,3-glucanase in culture, and induced chitinase in plants. Soaking R. solani sclerotia in either bacteria-free culture filtrates or in sap extracted from plants treated with Pseudomonas strains PF1 and FP7 or inoculated with R. solani significantly reduced the germination capacity of the sclerotia. The inability of treated sclerotia to cause sheath blight symptoms indicated loss of virulence. In all the experiments strain PF1 or FP7 always performed better than PB2. The 35 kDa chitinase induced by Pseudomonas in rice plants was purified and its antifungal activity against mycelium and sclerotia of R. solani was demonstrated. The production of antibiotics, antifungal compounds, bacterial lytic enzymes and the induction of plant chitinase were correlated with antifungal activity against R. solani sclerotia.